Implementation of Notary Services and Education In Providing Legal Services for Poor People Based on the Notary Office Act - Tjandraningsih, Dewi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The research aims to analyze the criteria for people who can't afford to get legal services from a notary. To carry out the obligation to provide legal services to poor people. Normative qualitative research methods will describe the phenomena occurring in the field. Data collection techniques by conducting interviews. Observations at the location to be examined, with focused and thorough research and discussion focus, on the occurred findings. As for the study of documentation in the archives regarding regulations and obligations as a notary. The results of the research are (1). They are providing educational services for underprivileged people to get free legal services from a notary to people experiencing Poverty, as evidenced by a Certificate of Inadequacy from the Kelurahan, based on the client's acknowledgment that he is truly incapacitated, seen from the legal actions brought by the client to the Notary, personal assessment of the Notary based on the client's attitude and behavior when facing. (2). Notaries apply the obligation to provide education and legal services to poor people by providing free legal service assistance for their notary services, based on Article 37 paragraph (1) of Law Number 2 of 2014. Concerning the Position of Notary, but still charges a fee that must be incurred by the client, such as the cost of Non-Tax State Revenue.